Hadot Among the Medievalists: Revisiting the Historiography on “Intellectual Felicity” in the Thirteenth Century - Matteo Johannes Stettler (Eidos. A Journal for Philosophy of Culture)
The reception of Hadot’s work on the tradition of spiritual exercises among historians of medieval philosophy has rarely produced the results one might reasonably have expected. In this revisitation of the historiography on the notion of “intellectual felicity,” I thus hope to be able first to provide a corrective to the faulty understanding that some medievalists still seem to have of Hadot’s contribution to the study of philosophy as a way of life in the Middle Ages, and second, to show how ongoing debates in medievalist circles might point us toward the possible limitations with Hadot’s own understanding of philosophy as a way of life and its history in and beyond the Middle Ages.